Low-frequency closed-form expressions for crosstalk between twisted wire pairs - Lansink Rotgerink, J.H.G.J.; Verpoorte, J. (IEEE, 2016)
Crosstalk between two twisted wire pairs of equal and unequal twist rate is analysed and compared. Low-frequency approximations to the Multi-conductor Transmission Line equations are used to derive closed-form expressions for near-end crosstalk. Such analysis on cable configurations with different twist scenarios gives insight into sensitivity on relevant twist parameters as well as dependencies of crosstalk on all other model parameters. Results show that crosstalk between twisted pairs of equal twist rate behaves similar to that between untwisted wire pairs. On the contrary, an ideal combination of twisted pairs, by for instance doubling the twist rate in one of the pairs, causes crosstalk to vanish up to linear order. The performed analysis and derived closed-form expressions agree to measured crosstalk results and can lead to good understanding of upper and lower boundaries for crosstalk in different cable configurations.